2001
DOI: 10.1007/s002540100386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fundamental differences between batch and miscible displacement techniques on sorption distribution coefficient

Abstract: A circulation-through-column (CTC) technique was developed and employed to evaluate the in¯uence of fundamental differences between batch and miscible displacement (MD) techniques on the value of the sorption distribution coef®cient (K). Batch, MD, and CTC experiments were conducted to determine sorption equilibrium parameters for dimethylphthalate (DMP), diethylphthalate (DEP), and dipropylphthalate (DPP) using two natural soil samples with 0.36 and 1.48% organic carbon. Batch sorption isotherms of DMP and DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…Several studies have reported discrepancies between the K values of organic compounds determined by batch and column techniques. In most cases, the batch-determined values were higher than their column-determined counterparts (Bilkert and Rao 1985;Celorie et al 1989;Gaber et al 1992;Piatt et al 1996;Maraqa et al 1998Maraqa et al , 2011Maraqa 2001a;Thorbjarnarson and Mackay 1994b;MacIntyre et al 1991;Carmichael et al 1999;Bouchard et al 1988;Perillo et al 1998;Thomsen et al 1999;Kazemi et al 2008;Hanna et al 2012). The level of discrepancy between the batch-and column-determined K varies from slight differences (Bouchard et al 1988;Celorie et al 1989;Maraqa et al 1998;Maraqa 2001a) to differences that reached orders of magnitude (Piatt et al 1996).…”
Section: Relevance To Previous Studiesmentioning
confidence: 77%
See 3 more Smart Citations
“…Several studies have reported discrepancies between the K values of organic compounds determined by batch and column techniques. In most cases, the batch-determined values were higher than their column-determined counterparts (Bilkert and Rao 1985;Celorie et al 1989;Gaber et al 1992;Piatt et al 1996;Maraqa et al 1998Maraqa et al , 2011Maraqa 2001a;Thorbjarnarson and Mackay 1994b;MacIntyre et al 1991;Carmichael et al 1999;Bouchard et al 1988;Perillo et al 1998;Thomsen et al 1999;Kazemi et al 2008;Hanna et al 2012). The level of discrepancy between the batch-and column-determined K varies from slight differences (Bouchard et al 1988;Celorie et al 1989;Maraqa et al 1998;Maraqa 2001a) to differences that reached orders of magnitude (Piatt et al 1996).…”
Section: Relevance To Previous Studiesmentioning
confidence: 77%
“…This method was used by Maraqa (2001a) for the determination of K for few phthalate esters. Results obtained by this method were found to be comparable to those obtained from batch isotherm experiments Maraqa (2001a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No caso do imazaquin, a sua difusão em partículas minerais do solo não pode ser completamente descartada. A molécula apresenta dois grupos funcionais ionizáveis: um grupo carboxílico (ácido, pK a = 3,8) e um grupo quinolina (básico, pk a = 2,0) (Stougaard et al, 1990 (Gonzalez & Ukrainczyk, 1999;Maraqa, 2001). Esta discrepância tem sido atribuída a diversos fatores: (a) no deslocamento miscível, o contato entre o soluto e o sorvente é menor, quando comparado ao método "batch"; (b) o tempo para promover o equilíbrio químico geralmente é menor no deslocamento miscível.…”
Section: Parâmetros De Transporteunclassified